2021
DOI: 10.1017/dsj.2021.17
|View full text |Cite
|
Sign up to set email alerts
|

A meta-synthesis of the use of activity theory in design for sustainable behaviour

Abstract: Over the past decade, the field of design for sustainable behaviour (DfSB) has gained a growing amount of research interest. However, as the field evolves, new challenges also arise. A suitable unit of analysis is needed to contextualize users’ behaviour issues in a broader socio-cultural and long-term perspective. This paper explores the use of activity theory (AT) as a potential lens for guiding empirical analysis and design exploration in DfSB. By employing a meta-synthesis approach, we systematically searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 73 publications
0
1
0
Order By: Relevance
“…Although the TPB and PT have provided valuable insights into the field of consumer behaviours and perceptions in packagingfree systems, it should consider the potential contribution of activity theory (AT) as an alternative and complementary theoretical framework. AT introduces a lens that considers the interactions between human activities, social contexts and the role of artefacts as it is explored in the research by Wanjun et al [74]. AT can focus on mediating the effects of artefacts aligned with the material aspects of packaging-free systems, such as reusable containers and bulk dispensers, which play a crucial role in shaping consumer behaviours.…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the TPB and PT have provided valuable insights into the field of consumer behaviours and perceptions in packagingfree systems, it should consider the potential contribution of activity theory (AT) as an alternative and complementary theoretical framework. AT introduces a lens that considers the interactions between human activities, social contexts and the role of artefacts as it is explored in the research by Wanjun et al [74]. AT can focus on mediating the effects of artefacts aligned with the material aspects of packaging-free systems, such as reusable containers and bulk dispensers, which play a crucial role in shaping consumer behaviours.…”
Section: Theoretical Perspectivesmentioning
confidence: 99%
“…A broader application of the theoretical framework employed in the literature: Although the literature has predominantly used the TPB and PT to study consumer behaviours and perceptions in grocery habits and packaging-free systems, there is a clear possibility for adopting AT to broaden these perspectives. AT is another lens in the area of environmentally sustainable interventions that can be used to analyse consumer doings, enabling to finding of tensions and contradictions between the artefact and the user in a set context [74]. By incorporating AT, this research area can gain a broader perspective that extends beyond individual attitudes and social practices, looking into the complexity of how consumers engage in environmentally sustainable behaviours within complex systems [74].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The theoretical framework for the study consists of the overarching theory of the activity theory (AT) that was discussed in Chapter 1. Chu, Glad andWever (2021, p. 3, cited in Kaptelinin &Nardi 2006) stated that the work carried out by psychologists Lev Vygotsky and Sergei Rubinshtein in the 1920s and 1930s, when they sought an understanding of how the complex relationship between the human mind and society manifests in human activities, indicates the conceptual origin of the AT. , cited in Chu et al 2021) indicated that 'AT has the conceptual and methodological potential to be a pathbreaker in studies that help humans gain control over their artifacts'.…”
Section: The Theoretical and Conceptual Framework For The Chaptermentioning
confidence: 99%
“…Given the focus of this paper, we don't intend to present these theoretical lenses in detail. A comparison of the three theoretical lenses from a sustainable design perceptive can be found in [7][8][9][10]. How to make users become more willingly to mitigate the underlying product impacts, thus achieving pre-defined sustainability goals?…”
mentioning
confidence: 99%